Embryonic Stem Cells The Hormonal Regulation of Pluripotency and Embryogenesis - Atwood, Craig (IntechOpen, 2011)
Pluripotency is a prerequisite for the subsequent coordinated differentiation of embryonic stem cells into all tissues of the body. This book describes recent advances in our understanding of pluripotency and the hormonal regulation of embryonic stem cell differentiation into tissue types derived from the ectoderm, mesoderm and endoderm.